Implementasi Malicious Traffic Untuk Mendeteksi Serangan Siber di SMK Muhammadiyah 1 Yogyakarta - Hariyadi, Dedy; Kusumaningtyas, Kartikadyota; Muktamar, Burhan Alfironi (INTEK : Jurnal Informatika dan Teknologi Informasi, 2023)
The Covid-19 pandemic has had a positive impact including the increasing implementation of information technology in various fields including the education sector. One of them is the increasing use of mobile devices such as cell phones or tote computers that utilize wireless networks. Connecting devices via wireless networks has a serious impact on the potential threat of cyber attacks. The potential threat of cyberattacks on devices during the Covid-19 pandemic is increasing, this is indicated by 975 million anomalous traffic recorded by Badan Siber dan Sandi Negara (BSSN) in 2022. To identify these potential threats, a sensor is needed on the internal network. In this research, it is proposed to implement a cyber attack sensor to detect these potential threats. Based on network traffic monitoring, this research shows that there is a potential for data leakage originating from cell phones. Therefore, the potential for data leakage from cell phones or other devices needs to be evaluated to secure computer systems and networks.